STUDI PELAYANAN PUBLIK : PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT UMUM DAERAH (RSUD) TELUK KUANTAN KABUPATEN KUANTAN SINGINGI TAHUN 2016 - Vabella Mira Besta; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The government is responsible for meeting all the needs of decent health services for the community. The government's policy to meet the needs of the community in health services is the existence of the Social Security Administering Agency (BPJS) Health. In Kuantan Singingi Regency there is the only hospital with type C that is District General Hospital (RSUD) Teluk Kuantan which is a regional technical institution as health service provider in cooperation with Social Security Administering Body (BPJS) Health.The purpose of this study is to determine (1) Quality of service for participants BPJS Health at Regional General Hospital (RSUD) Teluk Kuantan Year 2016. (2) Factors that affect the quality of service for participants BPJS Health at Regional General Hospital (RSUD) Teluk Kuantan Year 2016. Type of research used is descriptive research using qualitative approach. Data analysis used is qualitative data analysis.The results showed that the quality of service for participants BPJS Health at Regional General Hospital (RSUD) Teluk Kuantan in 2016 can be said not good. Facts found in the field are facilities and infrastructure and medical support equipment is still inadequate, drug supply is also very limited, in providing services Doctors and Nurses are not friendly and still found differences in service provided by the hospital to patients BPJS Health. Service is also not timely and officers are still less responsive in serving patients. Factors affecting health services for patients BPJS Health in this hospital is the availability of facilities, human resources, funds and knowledge of the community.Keywords: Quality of Service, Hospital Service, BPJS